Many hands on this study: Development of a metonymy comprehension task - Siqueira, Maity; Melo, Tamara; Duarte Jr, Sergio; Baiocco, Laura; Ferrari, Caroline Girardi; Lopes, Nichele (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2023)
Metonymy is a pervasive linguistic/cognitive mechanism in everyday language. Still, studies assessing its comprehension are rare in the literature. Our goal is to present the elaboration of a verbal metonymy comprehension task in Brazilian Portuguese as well as test it using pilot studies. The task was based on the cognitive linguistics framework and psychometric guidelines were considered. The construction of the task considered psycholinguistic variables and included a conventionality task and an expert analysis. Three studies (N = 290, ages ranging 2 to 54 years old) were conducted until we reached a final version. The study resulted in a task composed of one practice item and six test items. Each item includes a sentence-stimulus and two questions (one open-ended and one closed-ended). Together, the items make up a raw score that represents metonymy comprehension. Data obtained from the pilot studies show that metonymy comprehension improves gradually with age and that there is a significant difference between items in both types of questions. This is in consonance with the literature, and thus points towards the instrument’s construct validity. The study results in a task that presents enough sensitivity to gauge comprehension of this phenomenon at different ages.